ENT SURGEONS AS MASTER TRAINERS OF CRICOTHYROIDOTOMY WILL SAVE PRECIOUS LIVES IN EMERGENCIES - Shabbir Bukhari, Syed Muhammad Asad; Aslam, Sohail; Riaz, Naeem; Abbas, Asim; Raza, Maqbool; Fareed, Ghulam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To train young doctors and paramedical staff on needle cricothyroidotomy and surgical cricothyroidotomy and provision of kits in trauma centers, main operation theatres and medical reception centers of the hospitals. Study Design: Quasi experimental study. Place and Duration of Study: Combined Military Hospital Peshawar and Pakistan Naval Ship Shifa, Karachi Pakistan, from Nov 2017 to Oct 2020. Methodology: Doctors and paramedical staff were selected on volunteer basis. Small groups were trained in 2-3hours. The participants were shown two videos of two procedures in Urdu language first and then were trained on mannequin. Results: A total of 345 participants including 205 males and 140 females were trained with mean age was 28.2667 ± 6.24 (SD) years. Out of 61 residents, 54 medical officers, 143 house officers, 35 nurses and 52 paramedical staff were participants. Conclusion: ENT surgeons must arrange mannequins and conduct training sessions of small groups after every 1 to 2 months.